2004
DOI: 10.1188/04.onf.985-988
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Denial

Abstract: Clinicians should not underestimate the value of the nurse-patient relationship when a patient is in denial. Patience, understanding, and self-awareness are crucial for providing a safe, trusting environment for patients who are experiencing denial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…This theory suggests that to actively cope with noncontrollable stressors could increase odds for maladjustment and psychological difficulties in several domains (Aldridge and Roesch, 2007; Schwartz et al, 2006). Therefore, a repressive coping style could be more adaptative in such circumstances (Stephenson, 2004). At highly stressful circumstances, this repressive style could help to focus on the task and not feel overwhelmed by emotions that could interfere with medical guidelines (Vos and De Haes, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This theory suggests that to actively cope with noncontrollable stressors could increase odds for maladjustment and psychological difficulties in several domains (Aldridge and Roesch, 2007; Schwartz et al, 2006). Therefore, a repressive coping style could be more adaptative in such circumstances (Stephenson, 2004). At highly stressful circumstances, this repressive style could help to focus on the task and not feel overwhelmed by emotions that could interfere with medical guidelines (Vos and De Haes, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of denial, inevitability, and helplessness support previous findings that this powerful emotion can result in difficulty in engaging with self-care and adherence to treatment particularly in chronic diseases [ 31 ]. It has been suggested that the diagnosis of a chronic illness can result in a reaction that resembles the stages of mourning, of which denial is a fundamental step, and that moving onto acceptance involves building a new identity [ 32 ]. Patience and understanding is needed to provide a safe and trusting environment to encouraging patients experiencing denial to develop a sense of autonomy in managing their diabetes [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the diagnosis of a chronic illness can result in a reaction that resembles the stages of mourning, of which denial is a fundamental step, and that moving onto acceptance involves building a new identity [32]. Patience and understanding is needed to provide a safe and trusting environment to encouraging patients experiencing denial to develop a sense of autonomy in managing their diabetes [31,33].…”
Section: Intrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, Lazarus (39) ya indicaba que no es correcto hablar de estrategias buenas o malas en términos absolutos, sino que la adecuación de éstas siempre deberá valorarse en función de las características de la situación estresante y de las características personales del individuo que le haga frente. En el ámbito de la psico-oncología se ha hablado de la utilidad de las estrategias de desvinculación cognitivo-conductual en diversos trabajos (40,41) . En ellos, se postulaba la utilidad de estrategias tales como la negación o la represión emocional, como elementos que, puntualmente, pueden favorecer el seguir centrado en una serie de objetivos relacionados con el tratamiento o las rutinas cotidianas y no dejar lugar a la tristeza y/o la depresión, que en muchos casos podría llegar a ser incapacitante o interferir con las pautas médicas (42) .…”
Section: Discusión Y Conclusionesunclassified